Patriotic and religious activity of the Gymnastic Society "Sokol" in the Polish lands (until 1939) - an outline - Renata Urban (Jan Długosz University in Częstochowa, 2023)
The Gymnastic Society "Sokol" ("Falcon") (hereinafter: GS "Sokol") was the first and for several years the only Polish organisation to obtain a permission from the authorities of the partitioning states to carry out its activities during the period of partitions. The first falcon nest was established in Lviv in 1867, with further nests being set up in the cities of the Austrian, Prussian and later Russian partitions. Although - as the name suggested - the GS "Sokoł" was a gymnastic association, other forms of activity also played a significant role in its programme of activity. Singing, reading and caring circles were formed in the nests and members of the GS "Sokoł" participated in religious and patriotic ceremonies, thus cultivating Polish national traditions. Evenings and rallies were organised, commemorating religious holidays and important events in the history of the Polish nation, which reminded us of common goals and ideals during the period of national captivity. "Sokol" took on the duty of teaching native speech and native history. The scope and nature of the patriotic and religious activity of the GS "Sokol" was best evidenced by the National Commandments and the National Sins which were contrasted with them. Their very name and number indicated deep religiousness of the falcons. It derived not only from the authentic faith of the members of the GS "Sokol" but from the ideology of the movement. In the tragic historical moments of national captivity they placed their hope in God and found solace in prayer. All Sokol celebrations as well as everyday activities of the GS "Sokol" were of a patrioticreligious nature.